2005
DOI: 10.2298/aci0501083p
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound (EUS) in staging and follow-up of patients with malt lymphoma treated conservatively

Abstract: EUS appears to be a sensitive procedure for initial staging and assessment of treatment response and long-term follow up in patients with gastric lymphoma. The importance of EUS lies in abbility to detect relapse early, too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Interestingly, Varas et al defined, in a subset of 24 patients, an accuracy of EUS in defining T factor of 91%, whereas the usage of miniprobes has given an accuracy of 88% and this mismatch was higher in evaluating the N factor confirming the high clinical impact of EUS (Varas et al, 2006). As a general rule, EUS has entered in the clinical practice of staging evaluation (Di Raimondo et al, 2007;Pavlović et al 2005) and has been indicated as an ''obligatory part of the staging procedure'' (Fischbach, 2010). Thus, in the 2010 ESMO guidelines (Zucca & Dreayler, 2010), EUS has been indicated as the most appropriate technique in defining the locoregional staging.…”
Section: Endoscopic Ultrasound In Staging Of Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, Varas et al defined, in a subset of 24 patients, an accuracy of EUS in defining T factor of 91%, whereas the usage of miniprobes has given an accuracy of 88% and this mismatch was higher in evaluating the N factor confirming the high clinical impact of EUS (Varas et al, 2006). As a general rule, EUS has entered in the clinical practice of staging evaluation (Di Raimondo et al, 2007;Pavlović et al 2005) and has been indicated as an ''obligatory part of the staging procedure'' (Fischbach, 2010). Thus, in the 2010 ESMO guidelines (Zucca & Dreayler, 2010), EUS has been indicated as the most appropriate technique in defining the locoregional staging.…”
Section: Endoscopic Ultrasound In Staging Of Diseasementioning
confidence: 99%
“…Before the introduction of HPeradication therapy, the presence of an early stage disease represented the major indicator of response to surgery, while in HP-eradication era it designates the response to the HPtherapy itself. Nevertheless, the most important factor in risk assessment remains the loco regional staging and EUS preserves a great importance due to the fact that it is able to indicate, with accuracy superior to other techniques, the precise loco-regional stage of disease and consequently the required treatment (Pavlović et al 2005). Indeed, PGL of MALT type, when confined to mucosa and sub-mucosa layers responds to HP eradication therapy without any need of chemotherapy, meanwhile DLBCL are usually treated as general disease with chemo-immuno-therapy, even if recent case reports indicated the regression of locally staged DLBCL after HP eradication (Montalban et al, 2001, Tari et al, 2009.…”
Section: Prognostic Assessment and Treatment: How Endoscopic Ultrasoumentioning
confidence: 99%
See 2 more Smart Citations
“…However, the importance of EUS in follow‐up evaluation is controversial . During the last decade, some reports have indicated the importance of EUS in evaluating the response to treatment and long‐term follow‐up of gastric lymphomas with limited disease and in patients with local‐advanced MALT lymphoma . However, other studies have not confirmed these results and have indicated that the achievement of a complete response by EUS takes much more time than the demonstration of a complete response by endoscopic biopsy .…”
Section: Introductionmentioning
confidence: 99%